Digital health literacy and online information queries in Portuguese university students. (20th October 2021) - Rosário, R; Augusto, C; Silva, MJ; Martins, S; Duarte, A; Ramos, N; Martins, MRO; Fronteira, I
Abstract: Background: Worldwide there is an overwhelming amount of information about COVID-19 circulating online, also named infodemic. Misinformation (the unintentional) and disinformation (the intentional) spreading of false information have proven to be very dangerous to public health. Hence, more than ever, people need skills for searching, evaluating and integrating information related to health in daily life, i.e., health literacy. Until now, little is known about the digital health literacy of university students and their information-seeking behaviour. Hence, this study aimed to analyse the associations between university students' digital health literacy and online information queries during the beginning of the COVID-19 pandemic (and infodemic) in Portugal. Methods: A cross-sectional study of 3.084 Portuguese university students (75.7% females), with an average age of 24.2 (SD = 7.5), was conducted using an online survey. We used sociodemographic data (sex, age, subjective social status) and the digital health literacy questionnaire adapted to the specific COVID-19 context. Online information queries included the topics related to SARS-CoV-2 and COVID-19 searched by students. Logistic regression models were performed. Results: Online information queries (e.g., individual measures to protect against infection, current spread of the virus, current situation assessments and recommendations) were associated with an increased odds of achieving sufficient digital health literacy. Conclusions: Online information queries related to epidemiological and public health topics are significantly associated with digital health literacy in times of COVID-19. Further studies are needed, including programs that improve digital health literacy among university students and increase the availability of high-quality content information.